“STATICS” AND “DYNAMICS” SCHUMPETERIAN PARADIGM OF ECONOMIC SYSTEM AND ITS PRACTICAL IMPLICATION - Y. Bazhal (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
This paper analyzes fundamental features of Schumpeter’s theory of economic development which distinguish two different types of economy – statics and dynamics. Such methodology unlike of neoclassical approaches gives a new vision of driving forces of modern economic development with a crucial role of the innovation technological change.